Zoledronic acid: Pleiotropic anti-tumor mechanism and therapeutic outlook for osteosarcoma - Ouyang, Z.; Li, H.; Zhai, Z.; Xu, J.; Dass, Crispin; Qin, A.; Dai, K. (2018)
© 2018 Bentham Science Publishers. Background: Osteosarcoma is considered the most frequent primary bone malignancy. Lung metastasis is the leading cause of death and the most consistent factor for predicting negative patient outcome in osteosarcoma. Third-generation nitrogen-containing bisphosphonates, such as zoledronic acid, have been shown to reduce osteolysis induced by bone metastasis and exhibit highly selective localization and retention in bone, thus making them attractive agents in the treatment of bone metastasis. Studies have shown that zoledronic acid exerts pleiotropic anti-tumor effects against osteosarcoma cells in vitro, including anti-proliferative, anti-angiogenic, and immuno-modulatory effects. However, the efficacy of zoledronic acid against primary tumor growth and pulmonary metastasis of osteosarcoma is controversial, which has limited its clinical application. Objective: The present review summarizes the controversial effects of zoledronic acid on primary tumor burden and pulmonary metastases in osteosarcoma. We also analyze the clinical effectiveness of zoledronic acid alone and in combination with chemotherapeutic drugs for the treatment of osteosarcoma. Conclusion: Zoledronic acid exhibits diverse anti-tumor effects in osteosarcoma in vitro, however, the in vivo effect is still controversial. Further preclinical and clinical studies are needed to clarify the effects of zoledronic acid in osteosarcoma.